Building in-situ instruments for the Street Sonatas #1 and #5 - Roels, Hans (Revista Vórtex, 2021)
Musical work for the Dossier "A quarter of century of Pd: past, present and future" [note by editor] Link #1: https://youtube.com/playlist?list=PLXdYuKtwUhUrirWQ0B2X7XhfrBCGJVlGn